2019
DOI: 10.1002/ijc.32196
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer exosomes induce lymphatic network remodeling in lymph nodes

Abstract: The lymphatic network remodeling may guide tumor metastasis in a sentinel lymph node (SLN). Although tumor-derived exosomes have been demonstrated to modify the microenvironment in adjacent organs and initiate a premetastatic niche, their influence on the lymphatic network in SLNs has not been explained. Here, we show that CT26 cell exosomes (Exo) promote the proliferation of lymphatic endothelial cells and the formation of lymphatic network in SLN, facilitating the SLN metastasis of colorectal cancer (CRC). U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 32 publications
3
56
0
1
Order By: Relevance
“…Limitations of this work include the omission of lymphatic flow rates as a considered variable despite it being widely hypothesized that they are substantially changed in disease contexts ( Habenicht et al., 2017 ; Hinson et al., 2017 ; Ji, 2017 ; Otto et al., 2014 ; Stacker et al., 2014 ; Sun et al., 2019 ). Given that the dependencies of WSS on SCS height and volumetric flow rate are first versus second order, respectively, we focused instead on how small changes with respect to SCS height could influence cell interactions within the SCS under the influence of fluid flow.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of this work include the omission of lymphatic flow rates as a considered variable despite it being widely hypothesized that they are substantially changed in disease contexts ( Habenicht et al., 2017 ; Hinson et al., 2017 ; Ji, 2017 ; Otto et al., 2014 ; Stacker et al., 2014 ; Sun et al., 2019 ). Given that the dependencies of WSS on SCS height and volumetric flow rate are first versus second order, respectively, we focused instead on how small changes with respect to SCS height could influence cell interactions within the SCS under the influence of fluid flow.…”
Section: Discussionmentioning
confidence: 99%
“…45 In the same year, Sun et al reported that colon cancer-cell derived exosomes containing IRF-2 are taken up by the macrophages and induce VEGFC production, which then promotes lymph node metastasis through lymphatic endothelial cell proliferation and lymphatic vessel remodeling. 46…”
Section: Role Of Exosomes In the Enlargement Of Cancer Tissue With Anmentioning
confidence: 99%
“…Furthermore, tumor cell dissemination is guided by the lymphatic network. IRF-2 in exosomes derived from colon cancer lines promotes the proliferation of lymphatic endothelial cells and the formation of the lymphatic network in the sentinel lymph node, increasing the frequency of F4/80+ macrophages and promoting Vascular Endothelial Growth Factor C (VEGFC) secretion [63]. Similarly, miR-221-3p, CXCR4 or podopladin have been related to lymphangiogenesis in other tumors [100,101,102].…”
Section: Cross-talk Between Tumor and Microenvironmental Cells By mentioning
confidence: 99%
“…Dotted line represents separation between primary tumor and distal metastasis. References are shown in brackets [38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63]. Created with BioRender.com.…”
Section: Figurementioning
confidence: 99%